Wielką Reformę Teatru między bajki włożyć? - Karasińska, Marta (Wydawnictwo Naukowe UAM, 2007)
The phenomenon of the Great Theatre Reform which concerned the works of outstanding stagemanagers of the turn of the 19th century, preserved in our local humanistic tradition, does not exist as a separate phenomenon in the theatrological ideas in other countries. Observed for the first time in Poland by Leon Schiller, the movement of the revival of the European theatre, it is in direct relation with the modernistic breakthrough which occurred simultaneously and which superseded the Newtonian vision of the world with a new scientific paradigm - thermodynamics which revolutionised physics and Einstein's theory of relativity. The new conception of space and time and of motion, the instrumental role of an observer in creating phenomena was reflected in the artistic works of modernism, mostly in the stage art, which is the most "space and time" art of all - mainly in the theatrical works of Adolphe Appia and Gordon Craig.
Should the Great Reform of the Theatre be written off as fiction?